DEVELOPMENT OF MODERN INFORMATION COMPETENCE OF PRIMARY CLASS TEACHERS: DEVELOPMENT OF MODERN INFORMATION COMPETENCE OF PRIMARY CLASS TEACHERS - Hasanov, anvar (Физическое воспитание, спорт и здоровье, 2025)
This article is devoted to the issues of developing the modern informational component of future elementary school teachers studying in higher education. Effective and advanced methods of modern component development have been explained by the author.